Problems with administrative work of administrative staff in educational institutions Under the jurisdiction of Phra Nakhon Si Ayutthaya Primary Educational Service Area Office 1 - kitbumrung, philaiphorn; Montaisong, Teerawat (Mahachula Academic Journal, 2024)
Abstract The purposes of this research are to (1) study problems in the clerical work of administrative staff in educational institutions (2) study the guidelines for performing clerical work of administrative staff in educational institutions. There are two operational steps: Step 1: Study problems in the work of administrative staff in educational institutions. Step 2: Propose guidelines for the clerical work of administrative staff in educational institutions. The sample group consisted of 123 administrative staff. Research instruments It is a questionnaire with a reliability value of 0.94. Statistics used in data analysis include percentage, mean, and standard deviation. Step 2: Propose guidelines for the administrative work of administrative staff in educational institutions. The main information providers include: Five educational institution directors were selected through purposive selection. The tool used was a semi-structured interview. Data were analyzed using content analysis methods. The results of the research found that: 1) Problems with administrative work in educational institutions as a whole were at a high level. When considering each aspect, it was found that the logistics aspect had the highest average, followed by the information aspect. and other areas of work assigned by supervisors have low averages. 2) Solutions to solve administrative problems in educational institutions, consisting of 5 areas and 18 approaches as follows: 1) In the area of administrative work, there are 5 approaches, such as setting up a schedule for receiving and sending books so that officials The administration can deliver the books on time. 2) In terms of supplies, there are 4 approaches, such as educational institutions preparing/providing Manual for preparing supplies documents in accordance with the Government Procurement and Supplies Management Act B.E. 25640 3) In the area of information work, there are 3 approaches, for example, educational institutions must promote administrative staff. By providing training in preparing information both online and and offline To provide administrative staff with knowledge and understanding in preparing information in educational institutions. 4) In terms of coordination work, there are 3 approaches, such as educational institutions should promote administrative staff. By providing training Personality matters and continuous service both within and within the educational institution. 5) For other work assigned by supervisors, there are 3 approaches, such as the administrative officer summarizing meeting messages at the last meeting. and prepare the meeting agenda Keywords: administrative work; Administrative officer ; Ayutthaya Primary Education -Service Area Office 2